2016
DOI: 10.1002/pssr.201600080
|View full text |Cite
|
Sign up to set email alerts
|

Thermal activation and deactivation of grown‐in defects limiting the lifetime of float‐zone silicon

Abstract: By studying the minority carrier lifetime in recently manufactured commercially available n‐ and p‐type float‐zone (FZ) silicon from five leading suppliers, we observe a very large reduction in the bulk lifetime when FZ silicon is heat‐treated in the range 450–700 °C. Photoluminescence imaging of these samples at the wafer scale revealed concentric circular patterns, with higher recombination occurring in the centre, and far less around the periphery. Deep level transient spectroscopy measurements indicate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 14 publications
(35 reference statements)
8
81
0
Order By: Relevance
“…The lower lifetime level and the injection dependent lifetime curves of the Group IV samples (not shown) indicate an additional lifetime limitation due to other recombination active defects. This is in accordance with the observations of Grant et al 1 and indicates that the defects observed in this study are an additional defect species.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The lower lifetime level and the injection dependent lifetime curves of the Group IV samples (not shown) indicate an additional lifetime limitation due to other recombination active defects. This is in accordance with the observations of Grant et al 1 and indicates that the defects observed in this study are an additional defect species.…”
Section: Discussionsupporting
confidence: 94%
“…The phosphorus doped n-type samples featured a nominal thickness of 200 lm, while the boron doped p-type samples were 250 lm thick. After wet chemical cleaning, the samples were subjected to a thermal pretreatment in the form of an oxidation step at 1050 C for 60 min in order to homogenize thermal history and avoid influence of the bulk defect class discussed by Grant et al 1 We then address the wafer bulk as "stabilized" (e.g., in Fig. 1) as no changes of the wafer bulk lifetime due to temperature steps are expected after this treatment.…”
Section: Experiments a Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of the phosphosilicate glass in buffered HF and subsequent SC cleaning, the wafers were thermally oxidized in oxygen (with background dichloroethylene) for 60 min at 1050°C. The oxidation annihilates grown-in defects [35], [36] while the phosphorus diffusion getters impurities and prevents external contamination during the high-temperature oxidation. Following the high-temperature processing, the SiO 2 film and phosphorus diffused region were chemically etched away.…”
Section: Quantifying Surface Recombination Of Superacid-treated Simentioning
confidence: 99%
“…The implied assumption is that the material is free of any defects, which may not always be the case [20]. This assumption was nonetheless deemed preferable to the use of an arbitrary or variable bulk lifetime for comparison of surface passivation.…”
Section: Resultsmentioning
confidence: 99%